Desain dan Uji Coba Media Pembelajaran Aplikasi Android berupa Weblog Berbasis Contextual Teaching and Learning pada Materi Sistem Priodik Unsur - Aulia, Sherly; Utami, Lisa (Jurnal Riset Pendidikan Kimia (JRPK), 2021)
This research aimed at designing Android learning media application in the form of Contextual Teaching and Learning based Weblog on Periodic System of the Elements lesson. Research and Development (RnD) method was used in this research with Borg and Gall model that was limited to the fifth stage. Questionnaire that Rating scale with four ratings was used was arranged in the form of checklist. The research finding was Android learning media application in the form of Contextual Teaching and Learning based Weblog on Periodic System of the Elements lesson, and it was named as Kimia Pintar or it was shortened as KITA. Android learning media application in the form of Contextual Teaching and Learning based Weblog on Periodic System of the Elements lesson was stated proper, it was based on the research findings that the assessment percentage of media validation by the experts of material was 94% and 94.64% by the experts of media, the assessment criteria were very valid; the assessment percentage of teacher practicality test was 90% with very practical assessment criteria; and student response test was 40%, it was very good, 40% stated good and 20% stated normal. Keywords: Learning Media, Application, Android, Weblog, Contextual Teaching and Learning, Periodic System of the Elements